Lattice Dynamics in Organic Ferroelectrics Using Neutron Spectroscopy and Ab-Initio Modeling - Mukhopadhyay, Sanghamitra (Frontiers in Physics, 2022)
Lattice dynamics in organic ferroelectric PhMDA (2-phenylmalondialdehyde C9H8O2) has been investigated using inelastic neutron scattering (INS) spectroscopy and first principles based calculations. Most of the prominent features of the INS spectrum originated from the normal modes of hydrogen bonded malondialdehyde (MDA) units rather than from phenyl rings. It is also found that carbon-hydrogen bonds in the MDA unit are tighter than these in phenyl rings. From the calculated splitting of LO and TO normal modes, it is predicted that hydrogen bonds in MDA units, which hold the solid state structure, contribute more to the ferroelectric polarisation of PhMDA. Any distortion of H-ion in these hydrogen bonds thus affect ferroelectric properties of this material.